STUDY OF THE THINKING OF MUHAMMAD SYAHRUR AND M. QURAISH SHIHAB ABOUT THE CONCEPT OF POLYGAMY: (Study of Interpretation of Qs. An-nisa/4:3) - Muhammad Mukhtar; Mardia Mardia; Andika Aminuddin (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2023)
Polygamy is one issue that is always hot to study because it creates contradictions in understanding it. Some allow it absolutely, and some forbid it regardless of whether or not there are conditions that must be met for those who want to become polygamous. This research method is literature, which is carried out using literature related to the thoughts of Syahrur and M. Quraish Shihab. The data sources are primary data and secondary data. Syahrur requires that the second, third, and fourth wives be polygamous widows who already have orphans, and there must be a fear of being unable to do justice to the orphans. Syahrur adheres to the kitab ayat approach. Society (the government) determines whether polygamy is enforced or prohibited by looking at whether or not polygamy is required. Meanwhile, M. Quraish Shihab views polygamy as focused on the redaction of verses and involving the context and history of the verse's revelation. The polygamy verse does not indicate an order requiring the practice of polygamy but rather an alternative solution to individual problems.